Effects of Florfenicol on nirS-Type Denitrification Community Structure of Sediments in an Aquatic Microcosm Model - Tengyue Zhang; Junying Sun; Jinju Peng; Yuexia Ding; Yang Li; Haotian Ma; Mengbo Yu; Yi Ma (MDPI AG, 2023)
Florfenicol is one of the most widely used antibiotics in aquaculture and veterinary clinics because of its low side effects and strong bactericidal effect. A total of 45~60% of florfenicol is not absorbed by the animal body and accumulates in the aquatic environment through a variety of pathways, which affects denitrification. Indoor aquatic microcosm models were constructed and sediment samples were collected at different florfenicol concentrations (0.1, 1, 10, and 100 mg/L) on days 0, 7, 30, and 60 to extract the microbial genome DNA and determine the water properties. qPCR and amplicon sequencing were used to study the dynamic changes in the nirS gene and nirS-type denitrification community structure, diversity, and abundance, respectively. The results showed that high florfenicol stress influenced the sediment's physicochemical properties, reducing conductivity, alkaline dissolved nitrogen, and organic matter content. In addition, the abundance of nirS, a functional denitrification gene, increased obviously with increased florfenicol concentrations but decreased the diversity of nirS-type denitrification microorganisms. Proteobacteria was the dominant denitrifying phylum in the sediment. Our study provides a scientific basis for the rational use of florfenicol in aquaculture to maintain a healthy and stable microecological environment and also provides a preliminary understanding of the response characteristics of water denitrifying microorganisms to florfenicol exposure.